Bariatric surgery: Perceptual accuracy, body satisfaction and quality of life (Research, Society and Development, 2021)
The World Health Organization points to obesity as one of the biggest public health problems. When the conventional treatments based on diets with the restriction of caloric intake and practice of physical activities have not shown satisfactory results, in the most severe cases, bariatric surgery becomes indicative. Therefore, the work is relevant in view of the search for elucidating the relationship that the patient has with its body concerning the perceptual aspect as well as its quality of life. In this sense, this work aimed to evaluate the perceptual accuracy, body satisfaction and quality of patients’ life undergoing bariatric surgery. This is a cross-sectional study carried out with 305 patients from a medium-sized reference clinic in the execution of bariatric surgeries in the Midwest region of Minas Gerais. One scale was used to assess perceptual accuracy and body satisfaction and another one to assess quality of life. Descriptive and association analysis of data were performed. The study showed that there was distortion of body’s image and patients’ dissatisfaction with their bodies in the studied period. Quality of life was considered good in all areas. There was no time influence after surgery on the results. So, it can be said that bariatric surgery is effective in terms of quality of life, however the perceptive accuracy and satisfaction with body image demonstrate that it deserves greater attention due to the results found.